Analisis Faktor-Faktor yang Mempengaruhi Nilai Tanah sebagai Dasar Penilaian Niali Jual Obyek Pajak (NJOP) PBB di Kota Semarang - Adrian Sutawijaya (Universitas Islam Indonesia, 2004)
As long as the region autonomy demand that getting greater, the role of Pajak Bumi dan Bangunan (property tax) will determine the region autonomy itself. Pajak Bumi dan Bangunan is one of the potential region income resources, because the object of taxes have a clear form and in the longer term the (Nilai Jual Obyek Pajak NJOP) that is a basis of cal¬culation on Pajak Bumi dan Bangunan will also increase together with the region economi¬cal development itself.Due to the theory given, there is a model that has been taken. The purpose is to study the influence of population density factor, location factor that reflected from the distance of land property to the centre town, the other factor that reflected in its accessibility, such as the width of the road, road condition, transportation facilities given and the last is free of flood environment variable that has a significant effect to the value of land property.The area of this research is consist of six Kecamatan (sub district), they are Keca¬matan Semarang Tengah, Kecamatan Semarang Selatan, Kecamatan Semarang Timur, Ke¬camatan Semarang Utara, Kecamatan Semarang Barat, Kecamatan Candisari with total sample area 100 (one hundred). The data was analysed with the multiplier linear regression model, then be applied with log natural model by using ordinary least squares model. Then result of regression is tested according to the theoretical, statistical, and econometrical cri¬teria.The result of this research is the population density factor will give the positive influ¬ence as 0,299 %. The distance factor will give a negative effect to the value of land as 0,162 % if the distance increase for 1 %. The width of road will give positive effect to the land val¬ues as 0,402 % if the road increase 1 %. Road condition will give positive effect to the lasund value as 0,208 % if there is a public transportation facility in the object location. While the last factor is free of flood that will give positive effect to the land value as 0,212 % if there is no flood in the object location.Keywords: land value, NJOP, PBB, local autonomy.